Fiji Islands: Failure of Constitutionalism? - Hughes, Robert (Victoria University of Wellington Law Review, 2001)
On 19 May 2000 Fiji experienced its third coup in 15 years when a group lead by George Speight took hostage members of the People’s Coalition government. While the coup itself was "a qualified failure", the aftermath left the constitutional situation in Fiji again in crisis. In this article, the author traces the historical, political, economic and legal factors relevant to the current constitutional situation in Fiji. The author then analyses the predominate constitutional issues facing Fiji. The author suggests that what is urgent is not so much an increased accommodation of indigenous interests in the written constitution, but rather the establishment of some sense of national identity capable of sustaining central government.